1996
DOI: 10.1046/j.1365-2958.1996.6201335.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of lambda integrase synthesis by rare arginine tRNA

Abstract: Lambda's int gene contains an anomalously high frequency of the rare arginine codons AGA and AGG when compared to genes of Escherichia coli or to the rest of phage lambda. These are the least frequent codons in genes of E. coli and are recognized by the rarest tRNAs. The presence of these codons reduces the translation rate and, depending on the context, this can strongly modulate translational efficiency by a variety of mechanisms. In this study, we show that expression of the natural int gene may also be mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 33 publications
(65 reference statements)
2
35
0
Order By: Relevance
“…Two codons, AGA (Arg) and AUA (Ile), are rarely used in E. coli but employed more frequently in coliphage . It has been noted that the integrase has a higher proportion of the rare arginine codons AGA and AGG and that this influences expression of this gene (74). Taking two pairs of proteins which one would expect to be expressed at different levels, capsid (orf6) and major tail protein (orf16), compared with repressor (orf69) and integrase (orf35), it was noted that certain codons are favored in the highly expressed genes.…”
Section: Indicated That the Fragments Were Arrayed C-a-g-i-h-d-e-b-f;mentioning
confidence: 99%
“…Two codons, AGA (Arg) and AUA (Ile), are rarely used in E. coli but employed more frequently in coliphage . It has been noted that the integrase has a higher proportion of the rare arginine codons AGA and AGG and that this influences expression of this gene (74). Taking two pairs of proteins which one would expect to be expressed at different levels, capsid (orf6) and major tail protein (orf16), compared with repressor (orf69) and integrase (orf35), it was noted that certain codons are favored in the highly expressed genes.…”
Section: Indicated That the Fragments Were Arrayed C-a-g-i-h-d-e-b-f;mentioning
confidence: 99%
“…Inhibition is most pronounced when the AGG cluster is in the AGG reading frame and near the 5Ј end of the coding sequence (23). Interestingly, this inhibitory effect is diminished or even abolished when the AGG codons are located in the middle of the gene (6) and is largely reversed by overexpression of tRNA Arg/UCU (7,35,36). These findings point to depletion of rare arginine-tRNAs by clusters of "hungry Arg codons" as the major cause of inhibition.…”
mentioning
confidence: 99%
“…Furthermore, others have shown that overexpression of cognate tRNAArg eliminates 5Ј-translational blockage caused by AGG codons (Chen and Inouye, 1994;Zahn and Landy, 1996). If the AGGs were simply having a structural effect on the mRNA inhibiting initiation, expression of the cognate tRNA would not have been expected to reverse the effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that inhibition of translation by AGG codons is a consequence of insufficient cognate tRNA, since supplying a plasmid expressing excess tRNA able to read these codons overcomes the inhibition (Brinkmann et al, 1989;Spanjaard et al, 1990;Chen and Inouye, 1994;Kane, 1995;Zahn and Landy, 1996). When ribosomes encounter a codon for which there is insufficient cognate tRNA (a 'hungry codon'), there are several alternative fates (reviewed in Parker, 1989), including mistranslation (reviewed in Kurland, 1992), frameshifting (Barak et al, 1996;also reviewed in Farabaugh, 1996) and probable stalling (for example, in attenuation mechanisms for amino acid biosynthetic operons; reviewed in Yanofsky, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation